Energy dissipation behaviours and seismic reduction performance of a proposed velocity and displacement dependent hydraulic damper (VDHD) - Sung, Wen-Pei; Shih, Ming-Hsiang; Zhao, Yu-Kuang (Journal of Civil Engineering and Management, 2010)
A new oil‐pressure Velocity and Displacement Dependent Hydraulic Damper (VDHD) is proposed by adding an additional Relief Valve parallel to the Throttle Valve with a different aperture size. This objective is to obtain an adaptive control by changing the damping coefficient of the VDHD for better control of structural movement during earthquake. In order to simulate its actual energy elimination, a mathematical analysis model is developed based on the Maxwell Model, which is modified by adding a serial friction model and a small damper parallel to the friction model in this study. The mathematical simulated results are compared with the actual energy‐dissipating behaviours of this proposed damper. The comparison shows that this proposed mathematical modelling could accurately simulate the relation of force and displacement as well as the relation of force and velocity during the process of energy dissipation. In addition, results of both the laboratory shaking table test and simulation analyses are used to test and verify the seismic reduction performance of this proposed damper. The experimental and simulation results show that in spite of the magnitude of the earthquake, the proposed VDHD device has a superior effect on the control of structural displacement by achieving effective acceleration reduction. First Published Online: 10 Feb 2011